Review on Geosynthetic Inclusions for the Enhancement of Ballasted Rail Tracks - Venuja, S.; Navaratnarajah, S.K.; Bandara, C.S.; Jayasinghe, J.A.S.C. (Springer, 2021)
Currently, there is an increasing demand for rail transport from a growing and urbanizing population worldwide as it is a resource-efﬁcient transport system. Moreover, its popularity among people is due to safety, reliability and economic proﬁt. The rail track system consists of rails, fastening systems, sleepers, ballast, sub- ballast and subgrade. Ballast is a highly angular coarse granular material which is the major load-bearing component as it transmits the stresses exerted by moving trains from sleepers to the subballast and subgrade at a reduced level. Ballast degradation is a major problem caused by the high dynamic and cyclic loads from faster and heavier trains as well as the impact loads due to wheel and rail irregularities and tracks at stiffness transition zones. It affects the track longevity together with the track geometry thereby a necessity of regular monitoring and maintenance. Ballast fouling is accompanied by ballast degradation as the broken ballast particles intrude into the voids of the ballast layer and obstruct the drainage. The popular method to reduce the excessive ballast deformation and degradation is the inclusion of geosynthetics such as geogrids, geotextiles, geocomposites, and geocells to the track foundation. This paper provides an extensive review of past studies on geosynthetics to reinforce the track foundation. In conclusion, this review presents the limitations of existing studies and provides recommendations for further studies.
Keywords: Rail track; Ballast; Degradation; Ballast fouling; Geosynthetics